2020
DOI: 10.1155/2020/3404168
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feed Forward Loop between Wnt/β-Catenin and NOX4 Promotes Silicon Dioxide-Induced Epithelial-Mesenchymal Transition of Lung Epithelial Cells

Abstract: Silicosis is a chronic fibrotic lung disease caused by the accumulation of silica dust in the distal lung. Canonical Wnt signaling and NADPH oxidase 4 (NOX4) have been demonstrated to play a crucial role in the pathogenesis of pulmonary fibrosis including silicosis. However, the underlying mechanisms of crosstalk between these two signalings are not fully understood. In the present study, we aimed to explore the interaction of Wnt/β-catenin and NOX4 of human epithelial cells in response to an exposure of silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Increased apoptosis was accompanied by the induction of SiO 2 [ 35 ]. JC-1 staining showed that SiO 2 induced epithelium cell apoptosis by depolarizing the mitochondrial membrane potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased apoptosis was accompanied by the induction of SiO 2 [ 35 ]. JC-1 staining showed that SiO 2 induced epithelium cell apoptosis by depolarizing the mitochondrial membrane potential.…”
Section: Resultsmentioning
confidence: 99%
“…The inhalation of respiratory silica dust can induce inflammatory responses, the secretion of inflammatory factors, and high ROS levels, which contribute to chronic lung injury [ 35 ]. It has been reported that metformin could inhibit the production of pro-inflammatory cytokines such as TNF-α from macrophages by inhibiting NF-κB [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inhalation of respiratory silica dust can induce in ammatory responses, the secretion of in ammatory factors, and high ROS levels, which contribute to chronic lung injury. [31] Importantly, the overproduction of intracellular ROS promotes the activation of alveolar macrophages and the secretion of pro-in ammatory cytokines, which aggravates lung dysfunction [49]. In this study, we found that SiO2 exposure signi cantly increased the level of intracellular ROS, which was effectively attenuated after the metformin treatment.…”
Section: Discussionmentioning
confidence: 61%
“…Increased apoptosis was accompanied by the induction of SiO2 [31]. JC-1 staining showed that SiO2 induced epithelium cell apoptosis by depolarizing the mitochondrial membrane potential.…”
Section: Metformin Attenuates Sio2-induced Cell Cytotoxicitymentioning
confidence: 91%
“…Adenoviral vectors expressing mouse Wnt3a (Ad.Wnt3a), Dkk1 (Ad.Dkk1), and adenoviral backbone vector control BglII (Ad.Bgl II) were kindly offered by Dr John F. Engelhardt at University of Iowa (Iowa City, Iowa, USA). 18 To investigate the role of Wnt signaling in regulation of inflammation-induced alveolar macrophages in vivo, LPS was used as the inducer of inflammation, mice were randomly divided into four groups with (3 males and three females, six mice per group): 1 Saline control, 2 Ad.BglII + LPS, 3 Ad.Wnt3a + LPS, 4 and Ad.Dkk1 + LPS. Each mouse was intratracheally instilled with saline, or 2.5 × 10 11 particles of adenoviral vector in a total volume of 25 μL PBS.…”
Section: Lps Challenge and Adenoviral Vector Delivery In Mouse Lungsmentioning
confidence: 99%